Determinants of livelihood choices and artisanal entrepreneurship in Nigeria. Issue 4 (4th June 2019) - Igwe, Paul Agu; Madichie, Nnamdi O.; Newbery, Robert
Abstract : Purpose: The purpose of this paper is to provide fresh insights into rural artisanal activities in a developing world context. It highlights key determinants of the decision to engage in an artisanal business and the challenges that impact upon the growth of these activities. Design/methodology/approach: The study adopts a mix-method research approach to explore a rural setting where most respondents (81 per cent) combine farm and non-farm livelihood activities. Quantitatively, a multi-nominal regression is used to examine the determinants of diversified artisanal livelihoods. It modelled the differences between farming livelihoods that have not diversified, compared to those also involved in the artisanal activity or wage employment and the intensity of participation. Findings: The findings show that nearly half of artisanal businesses (45.4 per cent) comprise only the owners and no employee, while 54.6 per cent employ one to three workers. Also, some artisanal ventures were more gender-specific than the gender-neutral activities. Other observations were in age (most artisans were under the age of 46 years) and vocational training (most were self-trained followed by a third receiving training only in specific areas such as technical works, building and construction and general trading apprenticeships). Research limitations/implications: The study is based on a relatively small sample size of 306 business owners, which makes it difficult to generalise despite the persuasiveness of the observations made. Practical implications: First, the use of econometric methods enabled the development of valid data sets (and various descriptive statistical and logit regression) to analyse determinants of the decision to engage in artisanal work, and the intensity of participation. Second, the ambiguity in categorising artisanal activities is unravelled. The study characterises the local artisanal sector and examines the intensity of participation. Without these, targeted support would remain elusive for practical and policy interventions. Originality/value: Artisanal activities constitute a high proportion of small businesses in the study area – with more than half (54.2 per cent) of respondents being classified as artisans, yet it is an overlooked area of entrepreneurship. Highlighted here are both types of activities and challenges regarding better conceptualising the understanding of artisans and regarding this mostly unarticulated base of practice.